The Impact of Viral Stealth Marketing on Consumers' Buying Interest on Cosmetic Products - Andi Dian Sry Rezki natsir; Riskawati Riskawati; Rianti Indah Lestari; Fitri Junianti; Anita Wardana (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
The concept of viral stealth marketing has been actively used by marketers to make products well received in society. Stealth marketing is one of the digital marketing strategies that advertises a product or service to someone, without them realizing that they are becoming a marketing object. Stealth Marketing is more commonly found on social media platforms today such as Facebook or Instagram compared to traditional advertising media such as newspaper, TV and radio broadcasts. Influencer as a service provider is becoming more general in this method of marketing. Cosmetic products are products that are often marketed with the viral stealth marketing method. Recommendations of cosmetic products from people we know will be easier to accept. Data collection was carried out by conducting a survey on the age group of Gen Z. Data processing using paired t-test and F-test. The results of the paired t-test found that there was a difference in the buying interest of consumers who received product promotion treatment (B1) with the group of consumers who received agent recognition treatment (B2) with a significance value of 0.000. Meanwhile, the results of the F-test show that the presence of agent recognition treatment affects consumers' buying interest in indicators of seeking information, trying products, knowing more, and the desire to own products. This result indicates a change in the buying interest of consumers to cosmetic products when they are aware of the use of viral stealth marketing promotion methods.